Error Analysis on Grammatical Aspects in The Students Writing Essay (Case Study At The Fourth Semester Students Of English Education Programme Of STKIP Taman Siswa Bima. - Sholihin Sholihin; Abd Haris (Fakultas Sastra - Universitas Muslim Indonesia, 2020)
The purpose of this study was to describe what kinds of error do the students in their writing essay and to describe the reasons why the students make the error in their writing essay at the four semester students of English education Programe of STKIP Taman Siswa Bima. This study applied case study method. The method unsuited to the error analysis procedures (following Chen, 2006:6) informed the processes to analyze the data consisted four steps were Data collection , Identification of errors, Classification of errors into error types, A statement of error frequency, Find out the case of error. The result of this research was concluded that the grammatical errors made by the fourth semester students of STKIP Taman Siswa Bima in writing essay are in Punctuation and Spelling for the highest errors 50.1%, the second is errors in Sentence Pattern 16%, followed by Auxiliaries 6,1%, Preposition 5.26%, Passive voice 4.48%, Verb Tense and Form 4.2%, Subject-verb agreement 4.0%, Articles 4%, Plurality 3.8%, Word order 2.3% and Pronoun 1,1% of 521 errors obtained from their essays. The cause of error based on interview was succession approximation system.